Assessment of Neuromuscular Function After Different Strength Training Protocols Using Tensiomyography. Issue 5 (May 2015) - de Paula Simola, Rauno Á.; Harms, Nico; Raeder, Christian; Kellmann, Michael; Meyer, Tim; Pfeiffer, Mark; Ferrauti, Alexander
Abstract : Abstract: De Paula Simola, RÁ, Harms, N, Raeder, C, Kellmann, M, Meyer, T, Pfeiffer, M, and Ferrauti, A. Assessment of neuromuscular function after different strength training protocols using tensiomyography. J Strength Cond Res 29(5): 1339–1348, 2015—The purpose of the study was to analyze tensiomyography (TMG) sensitivity to changes in muscle force and neuromuscular function of the muscle rectus femoris (RF) using TMG muscle properties after 5 different lower-limb strength training protocols (multiple sets; DS = drop sets; eccentric overload; FW = flywheel; PL = plyometrics). After baseline measurements, 14 male strength trained athletes completed 1 squat training protocol per week over a 5-week period in a randomized controlled order. Maximal voluntary isometric contraction (MVIC), TMG measurements of maximal radial displacement of the muscle belly (Dm), contraction time between 10 and 90% of Dm (Tc), and mean muscle contraction velocities from the beginning until 10% (V10 ) and 90% of Dm (V90 ) were analyzed up to 0.5 (post-train), 24 (post-24), and 48 hours (post-48) after the training interventions. Significant analysis of variance main effects for measurement points were found for all TMG contractile properties and MVIC ( p < 0.01). Dm and V10 post-train values were significantly lower after protocols DS and FW compared with protocol PL ( p = 0.032 and 0.012, respectively). Dm, V10, and V90 decrements correlated significantly to the decreases in MVIC ( r = 0.64–0.67, p ⩽ 0.05). Some TMG muscle properties are sensitive to changes in muscle force, and different lower-limb strength training protocols lead to changes in neuromuscular function of RF. In addition, those protocols involving high and eccentric load and a high total time under tension may induce higher changes in TMG muscle properties.